Association of soluble interleukin‐2 receptor α and tumour necrosis factor receptor 1 with heart failure: The Multi‐Ethnic Study of Atherosclerosis. (10th March 2020) - Bakhshi, Hooman; Varadarajan, Vinithra; Ambale‐Venkatesh, Bharath; Meyghani, Zahra; Ostovaneh, Mohammad R.; Durda, Peter; Wu, Colin O.; Tracy, Russell P.; Cushman, Mary; Bluemke, David A.; Lima, João A.C.
Abstract: Aims: Soluble tumour necrosis factor‐α receptor 1 (sTNF‐αR1) and interleukin‐2 receptor α (sIL‐2Rα) predict incident heart failure (HF) in the elderly population. However, the association of these biomarkers with HF in a multi‐ethnic asymptomatic population is unclear. We aimed to investigate the association of sTNF‐αR1 and sIL‐2Rα with incident HF in a multi‐ethnic population of middle age and older participants. Methods and results: The multi‐ethnic study of atherosclerosis is a prospective population‐based study of 6814 participants aged 45–84 years who were free of clinical cardiovascular disease at enrolment. We included 2869 participants with available sTNF‐αR1 or sIL‐2Rα level measurement at baseline multi‐ethnic study of atherosclerosis exam (2000–2002). We used Cox proportional‐hazards model to investigate the association between sTNF‐αR1 and sIL‐2Rα with incident HF after adjusting for traditional cardiovascular risk factors and coronary artery calcium score measured by cardiac computed tomography. Among the included participants, the mean (standard deviation) age was 61.6 (10.2) years and 46.7% were men. The median (interquartile range) sTNF‐αR1 and sIL‐2Rα were 1293 (1107–1547) and 901 (727–1154) pg/mL. During a median follow‐up of 14.2 (interquartile range: 11.7–14.8) years, 130 participants developed HF. In multivariable analysis, the hazard ratio (95% confidence interval, P value) of incident HF for each standard deviation increment of log‐transformed sTNF‐αR1 and sIL‐2Rα was 1.43 (1.21–1.7, P ≤ 0.001) and 1.26 (1.04–1.53, P = 0.02), respectively. Excluding participants with interim coronary heart disease, we found a statistically significant association between sTNF‐αR1 and HF with hazard ratio of 1.39 (95% confidence interval: 1.11 to 1.74, P = 0.005) and sIL‐2Rα and HF showing a hazard ratio of 1.39 (95% confidence interval: 1.09 to 1.76, P = 0.007). Conclusions: sTNF‐αR1 and sIL‐2Rα are associated with a higher risk of incident HF in a multi‐ethnic cohort without a previous history of cardiovascular disease.